Ethnological Collections in Selected South African Museums - Past Issues and Current Challenges - Motsamayi, Mathodi Freddie (Museum and Society, 2020)
The paper examines the state of ethnological collections in two post-apartheid South African museums, with a specific focus on cataloguing, and is based, inter alia, on an appraisal of anthropological discourses that informed the collections. A discussion of the artefacts’ background is of importance in establishing their origins, motives for their presence in collections and the current state of these collections. Presently, such information is difficult to establish since persons who have knowledge regarding the makers, donors and collectors of artefacts are no longer part of the museums’ establishment. Evidently, curators face a huge challenge in cataloguing such materials with only patchy information available. In South Africa many ethnological collections of artefacts produced by Africans are 'owned' by heritage institutions, but the care expanded on the objects consists mainly in placing them in storeroom facilities where they are distant from custodians, devoid of identifying material, and insufficiently researched. I contend that the lacklustre manner of assessing items of indigenous material culture in museums of ethnography, and the accompanying decontextualization, are irreconcilable with their original socio-cultural and environmental significance, their meanings and technological trends. The question is what to do with museum collections of rare indigenous material culture, created in the colonial and apartheid era but which, unfortunately, are left without relevant information?